Country Partnership Framework for Belize for the Period FY18-22 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
The Country Partnership Framework (CPF) for Belize covers the period from July 1, 2017 to June 30, 2022 (FY18-22). It presents the World Bank Group’s (WBG) program and the anticipated results framework. It builds on the results and lessons of Belize’s first Country Partnership Strategy (CPS) that covered the period FY12-15. This CPF is well aligned with the Government’s long-term development vision, Horizon 2030: National Development Framework 2010-2030, and the thematic priorities emerging from the 2016 Belize Systematic Country Diagnostic (SCD). The overarching goal of the proposed CPF is to support Belize in strengthening its economic resilience. Recognizing the special characteristics of a small state with associated capacity and absorptive constraints, the CPF proposes a consolidated and focused program. This will be the second full strategy for Belize, with the engagement still maturing, and it factors in lessons from the implementation of the first strategy. Therefore, the CPF will retain flexibility in some elements of the engagement that will be further defined with the Government during implementation. The Performance and Learning Review (PLR) at mid-point will incorporate necessary adjustments including in the Results Framework. The CPF is organized around two focus areas: (a) fostering climate resilience and environmental sustainability; and (b) promoting Financial Inclusion and social resilience. To support these focus areas, the CPF envisages the implementation of a program that could reach up to US$30 million in new loans, subject to how program performance evolves in the course of the CPF period, continued Government interest in IBRD financing, and on IBRD’s lending capacity and demand from other borrowers. It will also be supported by non-lending instruments, notably Analytics and Advisory Services (ASAs), regional initiatives and trust fund resources.